Preparation and Evaluation of Bi-layer Floating Tablet of ydrochlorothiazide and Propranolol HCl - Pushkal Gupta; Ashwani Mishra; Anupam Pathak (Current Research in Pharmaceutical Sciences, 2015)
Bi-layer tablets consist of two layers which contain one or more drug. Sometimes it can be used to get modified release profile of the formulation by formulating individual layers using different sort of polymer. In this work attempt was made to formulate a tablet having one floating layer of Propranolol HCl and immediate release layer of Hydrochlorothiazide. Different concentration of carbopol, microcrystalline cellulose, sodium bicarbonate, citric acid sodium starch glycolate and Hydroxy propyl methyl cellulose were used to formulate bi layer tablets. Prepared formulations were evaluated for weight variation, friability, hardness, floating time and in vitro drug release .The best formulation F6 which passes all the evaluations was consider as the promising formulation of hydrochlorothiazide and Propranolol HCl.